Structure based reaction mechanism studies on periplasmic nitrate reductase - Melo, Diogo Filipe Monrroy Vilan e (2019)
The Periplasmic Nitrate Reductase (Nap) from Cupriavidus necator (Cn) belongs to the Dimethyl Sulfoxide (DMSO) Reductase family of mononuclear Mo-containing enzymes and catalyzes the reduction of nitrate to nitrite. The protein comprises a large catalytic subunit containing the Mo active site and one [4Fe-4S] cluster (NapA, 91kDa), and a small diheme c-type cytochrome subunit (NapB, 17kDa). In the present dissertation, the reaction mechanism of the Periplasmic Nitrate Reductase from Cupriavidus necator is studied by X-Ray Crystallography and complementary techniques like Thermal Shift Assays (TSA), Isothermal Titration Calorimetry (ITC) and Microscale Thermophoresis (MST). In the first crystallographic studies of Nap from Desulfovibrio desulfuricans (Dd), it was established that in the active site, the Mo atom was coordinated by two cis-dithioline groups, a sulfur from a cysteine side chain and a water/hydroxo ligand. Recently published crystal structures of Nap, particularly the structure of the heterodimeric Cn NapAB solved at high resolution (1.5 Å) and Dd NapA with bound ligands demonstrated that the sixth ligand is in fact a sulfur atom, contrary to the previous believed water/hydroxo ligand. Also, a partially reduced NapAB Cn crystal structure was obtained, where the coordinating Mo Cys thiolate is partially occupying a new conformation. The sixth sulfur ligand seems to have a partial disulfide bond with the Cys thiolate group, blocking nitrate from interacting directly with the Mo atom unless some rearrangement occurs during catalysis. Various crystal structures of NapAB from Cn co-crystallized with ligands are presented in this dissertation complemented by TSA, ITC and MST results. The results corroborate the existence of an alternate conformation of the coordinating Mo Cys thiolate and pave the way for more studies about the reaction mechanism of nitrate reductases.